Deconstructing Lecturer Performance Patterns Based on Longitudinal Data: An Educational Data Mining Approach Using K-Means Clustering` - Basrul Basrul; Samsul Bahri; Alim Misbullah (Universitas Muhammadiyah Surabaya, 2026)
Lecturer performance evaluation (EDOM) in higher education is often reduced to a single average score that fails to capture the heterogeneity of teaching competency profiles. This study deconstructs lecturer performance patterns through an Educational Data Mining (EDM) approach to overcome the